Sistema de aprendizagem com incidentes : desenvolvimento e implementação em um serviço de radioterapia - Radicchi, Lucas Augusto (Universidade Federal de São Carlos, 2017)
The process in healthcare may not produce desirable outcomes and strategies of risk minimization should be adopted to improve patient and professional safety. A risk management tool commonly used in high reliability industries (eg, aviation, nuclear power plants and petrochemicals) is incident learning, consisting of a systematic process of investigating deviations in the normal behavior of a system to extract information to improve their performance. This dissertation aims to develop an Incident Learning System (ILS), to implement it at a radiotherapy service in a cancer hospital and to analyze the critical success factors to use this tool. A literature review and an action research were carried out to implement the ILS, focusing on the perspective of the professionals involved. The records were analyzed by a multidisciplinary committee of professionals of the radiotherapy service (action research group) through a formal and structured process for investigation and classification (categorization) of the incidents. Based on the incidents analysis, the patient care process and the professionals working conditions were constantly evaluated critically and actions taken to reduce risk were proposed as a way to promote organizational learning. This was done by analyzing each incident individually and also by statistical analysis of the classification data, allowing identify patterns of performance common to the set of incidents. The greatest number of occurrences and detections of incidents occurred in the "Treatment" stage of the radiotherapy process. Major safety barriers, active and latent failures have been identified and improvement actions have been established for these most vulnerable areas. The ILS implementation process was constantly evaluated through participant observation, interviews and questionnaires, in order to improve the learning mechanisms. As a result of these evaluations and the review of the main implementation challenges observed in other publications in the area, a list of guidance issues was proposed to assist in the establishment of an ILS in the routine of a radiotherapy service.
Keywords: Radioterapia; Incidentes; Segurança; Aprendizagem; Radiotherapy; Incidents; Safety; Learning; ENGENHARIAS::ENGENHARIA DE PRODUCAO